Economic and Nutritional Security of Farmers through Mushroom Cultivation - Kaur, Prabhjot; Kumar, Pankaj (Indian Farming, 2021)
Agriculture is the backbone of Punjab economy. It has set new records of yield and production ofvarious field crops. Assured irrigation, quality seed of improved varieties, assured marketing ofcertain crops at MSP are some of the major factors for agriculture development in the state. Butall of these factors has also led to monoculture which is clearly visible from the prevalence of ricewheatcrop rotation. Sangrur distrct of Punjab is classical example where all of these events areevident. Sad part of the story is that the crop rotation has led to numerous problems related withproduction, sustainability, ecology, environmental pollution etc. This rotation produces a hugevolume of biomass in the shape of crop residue. On the one hand due to stagnated yield income ofthe farmers has no increment and on the other hand they are facing great difficulty in managingthe load of crop residue by different ways other than burning.